The Impact Of The Coronavirus Pandemic On Economic Sustainability: The Impact Of The Coronavirus Pandemic On Economic Sustainability - Bunga Aditi; Nani Nani (Jurnal Mantik, 2020)
This study was to find out and analyze the Coronavirus Pandemic Against Economic Sustainability of traders in Medan City. The method used in data analysis in solving this problem was a qualitative descriptive analysis. It formulated and interpreted data and information obtained from research objects by collecting, compiling, and interpreting data. The data was processed by the steps of making a data analysis plan, processing, analyzing, interpreting, and summarizing the data. In conducting the analysis, the data was collected by observations, interviews, and documentation. The research result showed that the impact of Coronavirus Pandemic on the Economic Sustainability of traders in Medan, it decreased sales as a result of the large number of people who did not dare to go out so that the visitors of Medan's market center became quiet. The instruction from the local government to limit the schedule for visitors to come to the center of the market resulted in reduced direct trader’s income. The conditions caused the comfort of the community disturbed and the number of people who worked from home by agencies resulted in reduced of community activities outside the home so that the impact on the condition of a market center was so quiet.